Calcareous sponges of the Western Indian Ocean and Red Sea - van Soest, Rob W.m.; de Voogd, Nicole J. (Zootaxa, 2018)
Past taxonomic studies of Western Indian Ocean and Red Sea Calcarea have been few and sporadic (e.g. Schuffner 1877, Jenkin 1908, Row 1909, Dendy 1913, 1916, Voigt et al. 2017, 2018). Nevertheless, approximately 70 species are known from these studies for the considered region, but the descriptions of the older records often lack sufficient details for reliable identification. We studied the Western Indian Ocean Calcarea collection kept in the Naturalis Biodiversity Center. Available specimens numbered 145, collected in the Red Sea, Seychelles, Maldives, Mayotte and Rodrigues, in addition to incidental samples from Oman, the Lakshadweep Islands, the Mozambique Channel, and Eastern South Africa. Using a combination of techniques (in situ and ‘on deck’ photography, detailed field notes, light microscopic studies and measurements, SEM microscopy, and selected DNA sequencing) we identified 45 species, divided over the two main classes Calcinea (24 spp.) and Calcaronea (21 spp.). Not all species could be definitely assigned to an already described or a new species, as seven remained qualified as ‘spec.’ or ‘aff.’ for reasons of insufficient material or lack of details of in situ habitus. Sixteen species appeared to be new to science: Borojevia voigti sp.nov., Borojevia tubulata sp.nov., Borojevia pirella sp.nov., Clathrina rodriguesensis sp.nov., Clathrina maremeccae sp.nov., Clathrina repens sp.nov., Leucascus schleyeri sp.nov., Leucetta sulcata sp.nov., Ute insulagemmae sp.nov., Leucandra pilula sp.nov., Leucandra mozambiquensis sp.nov., Grantessa woerheidei sp.nov., Sycettusa hirsutissima sp.nov., Vosmaeropsis glebula sp.nov., Paraleucilla erpenbecki sp.nov., and Kebira tetractinifera sp.nov. For a selection of the identified species from the Western Indian Ocean and the Red Sea (30 spp.), as well as from Indonesian material (22 spp.) published previously (see Van Soest & De Voogd 2015) we obtained sequences of the partial 28S gene of nuclear rDNA (C2–D2 region, cf. Voigt & Wörheide 2016). The sequences of the Western Indian Ocean and Red Sea species were used to assign these to genera and families based on a phylogenetic analysis using MEGA pack vs. 06.6 for Mac of the available dataset. The Indonesian sequences supplemented by partial 28S sequences taken from the Sponge Barcode Project website and the NCBI website were included in the phylogenetic analysis to confirm the assignments. The results were compared and discussed with additional information on regional Calcarea not represented in our material. The latter chapter yielded the discovery of a preoccupied name leading to Sycon oscari nom.nov. for a species described from Mauritius.